FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH MEMBUKA TABUNGAN HAJI DI BANK MUAMALAT INDONESIA CABANG SUNGAILIAT - Oktarini, Erlita (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
This study aims to determine the opening mechanism and influence factors Haj Savings excellent service, social and promotion to the customer's decision opened the Hajj Savings. Location of the study were examined by the authors focused in Bank Muamalat Indonesia Sungailiat branch. This research is a field research (field research) with quantitative research methods. The population in this study 518 while the sample 41 clients and using random sampling. While data collection techniques used were a questionnaire (questionnaire) and documentation. This study uses SPSS software version 18.0 and EViews version 4.1. Methods of data analysis used in this study is the instrument test questions using validity and reliability test, classic assumption test in the form of normality test, multicollinearity, autocorrelation and heteroscedasticity test, test data variables with multiple linear regression analysis and hypothesis testing with a partial test ( T test), simultaneous test (F test) and the coefficient of determination (test R)2 From the results of this study indicate that the test instrument known to question the validity of all the items is a valid question and test the reliability of all the variables is reliable. Classic assumption test revealed good overall. Based on the test variables and hypotheses that excellent service factor, collective social promotion and significantly influence the customer's decision. Partial test results concludes that the excellent service, social and promotion of positive and significant impact on customer decisions.